2023
DOI: 10.1126/scitranslmed.abq0603
|View full text |Cite
|
Sign up to set email alerts
|

Polymer nanoparticles deliver mRNA to the lung for mucosal vaccination

Abstract: An inhalable platform for messenger RNA (mRNA) therapeutics would enable minimally invasive and lung-targeted delivery for a host of pulmonary diseases. Development of lung-targeted mRNA therapeutics has been limited by poor transfection efficiency and risk of vehicle-induced pathology. Here, we report an inhalable polymer-based vehicle for delivery of therapeutic mRNAs to the lung. We optimized biodegradable poly(amine- co -ester) (PACE) polyplexes for mRNA delivery using end-group mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 86 publications
0
18
0
Order By: Relevance
“…Similar to P76, Suberi et al developed an inhalable polymeric mRNA delivery system for vaccination 92 by screening a library of different chemical end groups and poly(ethylene glycol) (PEG) content, along with amine conjugation to improve transfection efficiency. Although they found that PEGylated NPs had reduced transfection efficiency in vitro , they did additional in vivo screening to find the optimal PEG content.…”
Section: Recent Progress and Developmentmentioning
confidence: 99%
“…Similar to P76, Suberi et al developed an inhalable polymeric mRNA delivery system for vaccination 92 by screening a library of different chemical end groups and poly(ethylene glycol) (PEG) content, along with amine conjugation to improve transfection efficiency. Although they found that PEGylated NPs had reduced transfection efficiency in vitro , they did additional in vivo screening to find the optimal PEG content.…”
Section: Recent Progress and Developmentmentioning
confidence: 99%
“…167 Suberi et al further optimized protein expression after inhalation delivery to the respiratory tract by screening a library of delivery vectors with different modifications of amino-terminal groups and PEG content. 168 The mucus layer includes highly cross-linked mucin chains, water, and other gel-like components, forming a natural barrier. 169 At the same time, the highly negative charge of the lung mucus layer makes simple cationic polymer-carriers unable to pass through the mucus effectively.…”
Section: Biological Applicationmentioning
confidence: 99%
“…The successful development of mRNA vaccines against SARS-CoV-2 has transformed how researchers and clinicians perceive the use of mRNA as a therapeutic tool . Previously considered a theoretical approach, it has now become a promising and feasible option for clinical applications. , Particularly, mRNA has garnered significant attention in the field of pulmonology for its potential in treating inherited diseases, , including cystic fibrosis (CF) and α-1 antitrypsin deficiency as well as in the field of vaccinology for intranasal vaccination approaches . Accordingly, research exploring mRNA therapy for the pulmonary system has experienced rapid growth. , Nevertheless, the most significant challenge in its clinical translation lies in identifying a safe and effective delivery strategy .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Particularly, mRNA has garnered significant attention in the field of pulmonology for its potential in treating inherited diseases, 4,5 including cystic fibrosis (CF) and α-1 antitrypsin deficiency as well as in the field of vaccinology for intranasal vaccination approaches. 6 Accordingly, research exploring mRNA therapy for the pulmonary system has experienced rapid growth. 7,8 Nevertheless, the most significant challenge in its clinical translation lies in identifying a safe and effective delivery strategy.…”
Section: Introductionmentioning
confidence: 99%